Rapamycin attenuates gene expression of programmed cell death protein-ligand 1 and Foxp3 in the brain; a novel mechanism proposed for immunotherapy in the brain - Mostafa Khedri; Hamid Kooshki; Ramezan Ali Taheri (Wolters Kluwer Medknow Publications, 2021)
Background and purpose: Programmed cell death protein-1 (PD1) expresses on the cell surface of the activated lymphocytes and at least a subset of Foxp3+ regulatory T cells. The binding of PD1 to its ligands including PD-L1 and PD-L2 leads to deliver an inhibitory signal to the activated cells. Although PD1/PD-L signal deficiency can lead to failure in the self-tolerance and development of autoimmunity disorders, PD1 blockade with monoclonal antibodies is considered an effective strategy in cancer immunotherapy. Determining effective environmental factors such as stress conditions on the expression of PD1 and PD-L1 genes can provide an immunotherapeutic strategy to control PD1 signaling in the patients Mammalian target of rapamycin signaling is a stress-responsive pathway in the cells that can be blocked by rapamycin. In this study, the effects of rapamycin on the expression of immunoregulatory genes were investigated in the stress condition. Experimental approach: Daily administration of rapamycin (1.5 mg/kg per day) was used in the mouse model of restraint stress and the relative expression of PD1, PD-L1, and Foxp3 genes in the brain and spleen were evaluated using quantitative real-time polymerase chain reaction method. Findings/Results: With our observation, daily restraint stress ceased rapamycin to decrease the expression of Foxp3 in the brain significantly. These findings would be beneficial in developing tolerance to autoimmune diseases and finding immunopathology of stress in the CNS. In another observation, daily administration of rapamycin decreased the expression of PD-L1 in the brain cells of mice. In the spleen samples, significant alteration in genes of interest expression was not detected for all groups of the study. Conclusion and implications: Downregulation of the PD-L1 gene in the brain induced by rapamycin can be followed in future experiences for preventing immunosuppressive effects of PD/PD-L1 signal in the brain.